Tinjauan Hukum Islam Terhadap Jasa Titip Jual Beli Makanan Online Di Desa Tengguli Kecamatan Sajad Kabupaten Sambas - Nurul Najwa (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This study is motivated by differing opinions regarding the practice of online food delivery services (jasa titip). The research employs a qualitative approach with field research characteristics. The research approach used is a Normative-Sociological approach, which is based on a method that analyzes an object grounded in the laws and societal norms relevant to the discussion. Additionally, it examines the conditions in the field, particularly in the Tengguli Village government. To collect data, the researcher used interview guidelines and observation. Based on the results obtained in the field, it can be concluded that: 1) The practice of online food delivery services in Tengguli Village, Sajad District, Sambas Regency, through social media such as Facebook, has been able to provide full benefits to the buyers or customers using this service. This is because the actual practice or mechanism of the online food delivery service has been explained—customers order food in advance and pay an amount according to the details provided by the service provider. 2) From an Islamic legal perspective, the practice of online food delivery services is a transaction that brings benefits to the service providers, customers, and the food owners. This type of transaction is not considered selling someone else's property (known as bay’ al-fuduli), as the food owners voluntarily permit their food to be sold. The entire practice of online food delivery aligns with the principles of buying and selling, particularly the value of mutual assistance.)